(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Cervical cancer is one of the most common tumors of the female reproductive system. Among women in the Samarkand region, cervical cancer ranks third among reproductive system diseases, after breast cancer and ovarian cancer. In recent years, immunohistochemical methods have become increasingly important in assessing the biological characteristics of cervical cancer (CC), prognosing the disease’s course, and stratifying the risk of recurrence. Traditional clinical and morphological parameters, including FIGO stage, tumor size, depth of invasion, and lymph node status, do not always allow for an objective assessment of the tumor’s biological aggressiveness and the likelihood of an unfavorable outcome. In this regard, special attention is being paid to the study of immunohistochemical markers of cell proliferation, apoptosis, angiogenesis, immune response, and HPV-induced transformation. The most studied of these markers are Ki-67, p53, Bcl-2, VEGF, p16INK4a, and PD-L1. Their expression reflects the intensity of tumor growth, cell cycle disruptions, resistance to apoptosis, and the potential for tumor progression. In modern gynecological oncology, immunohistochemical markers are considered a promising tool for personalized recurrence risk prediction and treatment selection.